O conceito de pessoa como fundamento da ação humana de Cícero a Friedrich Heinrich Jacobi - Martone, Juliana F. (Revista de Estud(i)os sobre Fichte, 2024)
The aim of this article is to show how the concept of person, first coined by Cicero, reappears in a new guise in the work of philosopher Friedrich Heinrich Jacobi. It reappears as a way to justify his “non-philosophy” and, at the same time, to criticize the German philosophy of his time, especially transcendental philosophy. We will investigate what it means for Jacobi to affirm that philosophy is first and foremost history, that it is personal. In other words, to affirm that the way of living precedes the way of thinking. If history is the subject matter of philosophy, it cannot create its own subject matter (as would be the objective of transcendental philosophy). Jacobi recovers the notion of “philosopher” as it was conceived in Antiquity and puts back at the center of the debate of his time the wise Socratic non-knowledge, an art of living as the most authentic meaning of philosophy. To make this bold move, the concept of person is fundamental. It is at the center of Jacobi's philosophy and can be understood even better by comparing it with an opposing position: the notion of “philosophizing history of philosophy” defended by Kant, an ahistorical and a priori history, an archaeology of reason.